The importance of motor coordination abilities for performance in rhythmic gymnastics - Milovan Purenovic-Ivanovic, T.; Popovic, R.; Stankovic, D.; Bubanj, S. (Facta Universitatis: Series Physical Education and Sport, 2016)
Rhythmic gymnastics (RG) is a difficult and complex sport which requires increased space-time coordination between body movements and apparatus handling, thus making specific motor coordination a vital part of technical preparation in RG with an important role in creating the preconditions necessary for allowing the gymnast to learn many RG techniques. The purpose of the research was to test and/or determine the possibility of predicting success in RG performance on the basis of gymnasts` coordination skills. One hundred and twenty-seven national- and international-level rhythmic gymnasts (age: 11.93±3.09 years, body height: 147.65±14.6 cm, body mass:37.67±11.7 kg, BMI: 16.78±2.26 kg/m2, training experience: 5.85±2.81 years), distributed in five age categories (22 beginners, aged 7-9 years; 39 intermediate, aged 9-12 years; 26 advanced, aged 12-14 years; 25 juniors, aged 14-16 years; 15 seniors, aged 16 years and older), volunteered to participate in the study. Their baseline characteristics (age, body height, body mass, BMI, years of training experience, Success) were established, as well as their specific coordination skills (B-ROL, R-TCJ, H-SKP and C-JUG). By means of a Multiple regression analysis the specific coordination skills` statistically significant influence on Success was established only in the group of advanced and intermediate gymnasts (p<0.018 and p<0.000, respectively), with an explanation of 42%, i.e. 50% of success in RG. Also, the Regression analysis emphasized the significant independent contributions, to the prediction of the dependent variable, of three independent variables: ball rolling (intermediate gymnasts: p=0.03), hoop skipping (intermediate gymnasts: p=0.03 and sample in total: p=0.02) and clubs juggling (intermediate gymnasts: p=0.03 and sample in total: p=0.02), with positive relationship among these independent variables and dependent variable. This study has confirmed the importance of coordination skills for success in RG, but only for younger age categories.